P539 Unmet needs in advanced therapy-naïve (ATN) and advanced therapy-experienced (ATE) moderate-to-severe (mod-sev) ulcerative colitis (UC) patients in the United States (US). (27th May 2021) - Afzali, A; Kakehi, S; Lapensee, K; Lukanova, R; Hennessy, F; Knight, H; Singh, K
Abstract: Background: About a third of patients with mod-sev UC receiving advanced therapy (AT, i.e. biologics and tofacitinib) do not respond initially and another third lose response. We examined reasons for treatment choice and outcomes in ATN and ATE mod-sev UC patients. Methods: A point-in-time survey of US gastroenterologists and their respective consulting UC patients was conducted from Jan 2020–Feb 2021 (ongoing) using the Adelphi Disease Specific Programme™ for Inflammatory Bowel Disease. Physicians completed patient record forms for UC patients with a history of mod-sev disease covering treatment history and clinical status. Patients were classified as ATN and ATE based on treatment. Response to treatment status was identified by factor and cluster analyses using flare, remission and change in symptoms. Descriptive and comparative statistics were calculated for reasons for initiating/switching therapy and patient-reported outcomes (satisfaction, pain/fatigue, and quality of life via the EuroQol-5 dimension questionnaire [EQ-5D]). Results: Based on the interim sample, 66 physicians and 394 mod-sev UC patients were analysed. Of patients who were ATN (n=82) and ATE (n=312), 29% and 32% were classified as non-responders respectively. Comparing ATN vs ATE patients, mean age was directionally lower (38.4 vs 40.7 years), proportion of males was directionally higher (65% vs 55%), and mean time since diagnosis was similar (3.9 vs 3.8 years). In general, non-responders experienced gastrointestinal-related (90% vs 41%), anorectal (38% vs 6%), and fatigue-related symptoms (66% vs 23%) more frequently than responders. ATN patients eligible to receive AT (n=26) reported dislike of injections/infusions (46%) or unwillingness to go to infusion centres (31%) as reasons for not receiving AT. Most common reasons for switching therapy in ATN patients were disease progression (40%) and lack of tolerability (27%), and in ATE patients were loss of response over time (43%) and disease progression (35%). In the ATE group, patient and physician satisfaction rates were higher in responders vs non-responders (>93% vs <79%), pain and fatigue scores were lower (0.8 vs 2.3 and 1.1 vs 2.3, p<0.0001), and EQ-5D scores higher (0.93 vs 0.81, p=0.005). In the ATN group, comparisons were not conducted due to small sample sizes. Conclusion: In this point-in-time survey study with data collected during the COVID-19 pandemic period, about a third of mod-sev UC patients did not respond to current therapy. These results suggest an opportunity for new therapies that increase response rates, provide long-term disease control, provide alternatives to parenteral routes of administration, and enhance patient satisfaction.